The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1158/0008-5472.can-03-3084
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal Role of the Cell Death Factor BNIP3 in Ceramide-Induced Autophagic Cell Death in Malignant Glioma Cells

Abstract: The sphingolipid ceramide has been recognized as an important second messenger implicated in regulating diverse signaling pathways especially for apoptosis. Very little is known, however, about the molecular mechanisms underlying nonapoptotic cell death induced by ceramide. In the present study, we first demonstrate that ceramide induces nonapoptotic cell death in malignant glioma cells. The cell death was accompanied by several specific features characteristic of autophagy: presence of numerous autophagic vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
323
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 391 publications
(342 citation statements)
references
References 45 publications
15
323
1
3
Order By: Relevance
“…The diverse range of cellular responses elicited by an intracellular accumulation in the sphingolipid second messenger ceramide [3][4][5]7,8 are underscored by tissue specificity. It has been reported that treatment strategies utilized in the treatment of RMS (IR and chemotherapy) 27 require the generation of ceramide for apoptosis to be initialized as part of their tumoricidal action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diverse range of cellular responses elicited by an intracellular accumulation in the sphingolipid second messenger ceramide [3][4][5]7,8 are underscored by tissue specificity. It has been reported that treatment strategies utilized in the treatment of RMS (IR and chemotherapy) 27 require the generation of ceramide for apoptosis to be initialized as part of their tumoricidal action.…”
Section: Discussionmentioning
confidence: 99%
“…2 While the majority of studies evaluating the effects of an elevation in cellular ceramide have focused on its ability to induce apoptosis, 1,3 several other studies have also described ceramide to be necessary for the induction of senescence, 4 cell-cell interactions, 5 death receptor clustering 6 and autophagy. 7 Collectively these studies emphasize that the cellular response to elevations in ceramide are tissuespecific and that ceramide is capable of modulating several biochemical pathways. In this regard, data describing ceramide to mediate G 0 /G 1 arrest, 3,4,8 and to accumulate following the release of cells from G 2 /M arrest, 9 also implicate a role for ceramide in cell cycle progression and regulation.…”
mentioning
confidence: 99%
“…15 Treating cells with toxins that induce cell death, such as arsenic trioxide and cyanide, or with cellular products ceramide and amyloid-b also induce BNIP3 expression mediated by HIF-1 activation. 16,[12][13][14] In addition, transcription factor E2F-1 binds to the bnip3 promoter and induces its expression in rat ventricular myocytes. 17 Therefore, it is becoming apparent that many cellular stresses such as hypoxia or toxins lead to increased BNIP3 expression.…”
Section: How Is Bnip3 Expression Regulated?mentioning
confidence: 99%
“…29 Overexpression of BNIP3 can also induce autophagic cell death, measured by observation of autophagic vacuoles by EM, localization and processing of light chain 3 (LC3), which is a protein that is incorporated in autophagic membranes upon formation. 16,12,18,34 BNIP3-induced cell death is blocked by an inhibitor of autophagy (3-methyladenine), but not by an inhibitor of apoptosis (N-CBZ-Val-Aal-Asp(O-Me) fluoromethyl ketone). Knockdown of BNIP3 blocked hypoxia-induced autophagy and cell death, but did not block localization of LC3 with autophagosomes, therefore suggesting that BNIP3 is involved in autophagosome-lysosome fusion.…”
Section: Bnip3mentioning
confidence: 99%
“…For verification, cell death was analyzed by measuring the permeability of the cell membrane to AO staining as described in Materials and methods. The formation of acidic vesicular organelles (AVOs), is one of the characteristic features of cells which passes through the process of autophagy after exposure of different autophagy inducer agents (42,43). Autophagic vacuoles (AVOs) or autophagosomes are formed as a result of sequestering the parts of the cytoplasm or entire organelles respectively during the process of autophagy (31).…”
Section: Resultsmentioning
confidence: 99%